E-commerce and web technologies 12th international conference, EC-Web 2011, Toulouse, France, August 30 - September 1, 2011. proceedings - Huemer, Christian; Setzer, Thomas (Lecture notes in business information processing, 2011)
This book constitutes the refereed proceedings of the 12th International Conference on Electronic Commerce and Web Technologies (EC-Web) held in Toulouse, France, in August/September 2011. The 25 papers accepted for EC-Web, selected from 60 submissions, are organized into eight topical sections on semantic services, business processes and services, context-aware recommender systems, intelligent agents and e-negotiation systems, collaborative filtering and preference learning, social recommender systems, agent interaction and trust management, and innovative strategies for preference elicitation and profiling.